2010
DOI: 10.1007/s00247-010-1786-4
|View full text |Cite
|
Sign up to set email alerts
|

Role of plain abdominal radiographs in predicting type of congenital pouch colon

Abstract: Plain abdominal radiographs have a predictive value in determining the type of CPC and obviating the need for an invertogram.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 21 publications
0
15
0
1
Order By: Relevance
“…Such muscular deficiency along with raised intraluminal pressure is probably responsible for more frequent rupture of the rectum in ARM. A high incidence of bowel perforation in CPC [4,18] also favors the muscular deficiency theory. In a subset of ARM cases, restored transmural perfusion after relief of obstruction appears to precipitate an ischemia-reperfusion injury and perforation somewhat analogous to the pathogenesis of necrotizing enterocolitis.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Such muscular deficiency along with raised intraluminal pressure is probably responsible for more frequent rupture of the rectum in ARM. A high incidence of bowel perforation in CPC [4,18] also favors the muscular deficiency theory. In a subset of ARM cases, restored transmural perfusion after relief of obstruction appears to precipitate an ischemia-reperfusion injury and perforation somewhat analogous to the pathogenesis of necrotizing enterocolitis.…”
Section: Discussionmentioning
confidence: 84%
“…In a subset analysis, they found 2 perforations (9.5%) among 21 cases with delayed presentation of ARM. Mathur et al [18] recorded 5 perforations (6.5%) among 77 cases of ARM with congenital pouch colon (CPC). An Indian study [19] reported 2 perforations (1.6%) of 125 ARM, whereas a Japanese series [20] recorded 2 perforations (5.6%) in 36 cases of ARM.…”
Section: Discussionmentioning
confidence: 98%
“…The majority of cases of CPC have been reported from North India. [1] CPC was placed in the group of “rare/regional variants” of the Krickenbeck International classification. [7] The RA itself is a rare entity.…”
Section: Discussionmentioning
confidence: 99%
“…[1] In the abdominal radiograph, a single, large, dilated bowel loop with an air-fluid level occupying more than half of the total width of the abdominal cavity and displacing the small bowel to one side is usually diagnostic of CPC. Mathur et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation